The economics of patient safety Part III: Long-term care Valuing safety for the long haul - de Bienassis, Katherine (OECD Health Working Papers, 2020)
Long-term care (LTC) institutions are now providing care to a greater number of people, and more residents with chronic conditions and multiple co-morbidities, than ever before. Trends suggest this strain will continue to increase as OECD populations continue to age. The total cost of avoidable admissions to hospitals from LTC facilities in 2016 was almost USD 18 Billion, equivalent to 2.5% of all spending on hospital inpatient care or 4.4% of all spending on LTC. Research shows that over half of the harm that occurs in LTC is preventable, and over 40% of admissions to hospitals from LTC are avoidable. The root causes of these events can be addressed through improved prevention and safety practices and workforce development-including skill-mix and education. Targeted investments in a number of key areas can have a significant impact by mitigating the main cost drivers of adverse events in LTC.